PELATIHAN PEMASARAN MELALUI SUSTAINABLE PACKAGING YANG RAMAH LINGKUNGAN DI UMKM - Rediana Setiyani; Saringatun Mudrikan; Lyna Latifah (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
People really care about healthy food and are also starting to realize the impact of waste or packaging waste from processed food. Therefore, food entrepreneurs need marketing innovation, especially sustainable packaging that is environmentally friendly. The target of service activities is to improve marketing skills with sustainable packaging. The method applied consists of analyzing needs, creating service designs, providing assistance in implementing technology to partners and carrying out ongoing evaluation and monitoring activities to see partner developments before and after service. Technology transfer to partners is carried out theoretically by presenting material through oral presentations, followed by discussion and questions and answers, then continued with practice with mentoring. Based on the results of the training carried out, the potential for Kalisegoro MSMEs to switch to environmentally friendly packaging has very high potential. Some food preparations that were originally packaged using Styrofoam, mica and Thinkwall can be changed to using paper packaging. Processed food packaging in large quantities, which originally used mica, has switched to bamboo baskets.